Optical Tests on a Curve Fresnel Lens as Secondary Optics for Solar Troughs - D. Fontani; P. Sansoni; F. Francini; M. DeLucia; G. Pierucci; D. Jafrancesco (International Journal of Photoenergy)
A curve Fresnel lens is developed as secondary concentrator for solar parabolic troughs to reduce the number of photovoltaic cells. Specific measurements and optical tests are used to evaluate the optical features of manufactured samples. The cylindrical Fresnel lens transforms the focal line, produced by the primary mirror, into a series of focal points. The execution of special laboratory tests on some secondary concentrator samples is discussed in detail, illustrating the methodologies tailored to the specific case. Focusing tests are performed, illuminating different areas of the lens with solar divergence light and acquiring images on the plane of the photocell using a CMOS camera. Concentration measurements are carried out to select the best performing samples of curve Fresnel lens. The insertion of the secondary optics within the concentrating photovoltaic (CPV) trough doubles the solar concentration of the system. The mean concentration ratio is 1.73, 2.13, and 2.09 for the three tested lenses. The concentration ratio of the solar trough is 140 and approaches 300 after the introduction of the secondary lens.